ETHNO-TOURISM: PRESERVATION OF CULTURAL HERITAGE AND SUSTAINABLE DEVELOPMENT (European Journal of Interdisciplinary Research and Development, 2026)
The article analyzes the contribution of ethno-tourism to sustainable development, particularly in terms of supporting local economies, promoting cultural diversity, and encouraging community participation. Special attention is given to the opportunities and challenges associated with the development of ethno-tourism, including issues of authenticity, cultural commodification, and environmental sustainability.